A comparison between the Functional Analysis and the Causal-Loop Diagram to model inventive problems - Delgado Maciel, Jesus (2018)
The pressure of the market, the exigencies of the society, and the environmental restrictions ask for new problem-solving approaches. In this context, the Theory of Inventive Problem Solving (TRIZ) offers several advantages: it is a knowledge-based approach for problem-solving that links the problem requirements with some engineering models to guide the solving process. However, the learning process of TRIZ and its use with a practical purpose reveal many drawbacks. A significant problem, while using TRIZ, emerges when the user needs to analyze and formulate an inventive problem. To deal with this issue, a combination of TRIZ with other tools seems the best strategy. The use of the Functional Analysis (FA) is one of the best examples. Despite the usefulness of the FA technique, a difficulty remains: it is a complex task to model the causal relationship between several parameters or conditions within a system. However, a tool used in the System Dynamics Modeling deals well with this situation. The System Dynamics (SD) analyzes the nonlinear behavior of complex systems over time. Congruent with recent TRIZ advances, the SD is a computer aided-approach with an extended application domain, practically in any complex systemsocial, managerial, economic or natural system defined by some relationships, a flow of information, and some effects of causality. Hence, SD can produce useful information when there are several conflicts in a system, also called a problem network. SD uses a graphical tool to model the variables and states of a system: The Causal-Loop Diagram. This tool is helpful to explain a conflict, the change of a system, or merely the interactions that take place to obtain an effect. This article presents a comparison between the Functional Analysis and the Causal-loop Diagram to model inventive problems.